Development Strategy of Wealthy Customers in Chinese Commercial Banks - Zhou, Tianying (European Scientific Journal, ESJ, 2016)
Wealth management business is an old and young business. In terms of wealth management, it begins from the social class when wealth allocation becomes divided. Wealth management in modern sense originated in Napoleon Era in France. Napoleon gave his wealth to bankers of Switzerland to manage, which opened a precedent for wealth management. As far as Chinese commercial banks are concerned, wealth management business provides services to help wealthy customers realize the value of their assets. This paper reviews current situations of wealth management business in Chinese commercial banks and investigates customer development strategy.